Integration modeling and control of a 12-degree-of-freedom macro–micro dual parallel manipulator. (June 2022) - Lin, Jianfeng; Qi, Chenkun; Gao, Feng; Yue, Yi; Hu, Yan; Wu, Yuze
Parallel manipulator systems with large workspace and high-accuracy positioning are attractive for a variety of accuracy engineering applications. In this article, a new 12-DOF macro–micro dual parallel manipulator is presented, which comprises a 6-PSU macro symmetrical parallel manipulator and a 6-SPS micro orthogonal parallel manipulator. This novel mechanism can not only realize a large range of movement but also accurate positioning. To achieve high-accuracy control, a macro–micro integrated model of the macro–micro dual parallel mechanism is proposed, including a mechanical system model and drive system model. Aiming at the trajectory planning for a multi-degree-of-freedom (DOF) manipulator, a smooth optimization trajectory planner for the 12-DOF macro–micro dual parallel manipulator is presented to realize smooth trajectory generation. A high-accuracy motion controller combining feedback and feedforward is developed based on the drive system model. Finally, the experiment well validates the correctness of the integrated model and motion control algorithm and reveals that the proposed mechanism is expected to be adopted into micro scale manipulations.